Dysfunction of chromatin assembly factor 1 induces shortening of telomeres and loss of 45S rDNA in Arabidopsis thaliana - Mozgová, Iva; Mokros, Petr; Fajkus, Jirí (The Plant cell, 2010)
Chromatin Assembly Factor 1 (CAF1) is a three-subunit H3/H4 histone chaperone responsible for replication-dependent nucleosome assembly. It is composed of CAC 1-3 in yeast; p155, p60, and p48 in humans; and FASCIATA1 (FAS1), FAS2, and MULTICOPY SUPPRESSOR OF IRA1 in Arabidopsis thaliana. We report that disruption of CAF1 function by fas mutations in Arabidopsis results in telomere shortening and loss of 45S rDNA, while other repetitive sequences (5S rDNA, centromeric 180-bp repeat, CACTA, and Athila) are unaffected. Substantial telomere shortening occurs immediately after the loss of functional CAF1 and slows down at telomeres shortened to median lengths around 1 to 1.5 kb. The 45S rDNA loss is progressive, leaving 10 to 15% of the original number of repeats in the 5th generation of mutants affecting CAF1, but the level of the 45S rRNA transcripts is not altered in these mutants. Increasing severity of the fas phenotype is accompanied by accumulation of anaphase bridges, reduced viability, and plant sterility. Our results show that appropriate replication-dependent chromatin assembly is specifically required for stable maintenance of telomeres and 45S rDNA.
Keywords: Gene Expression Regulation, Plant; Chromatin Assembly Factor-1; mutace; Arabidopsis Proteins; DNA, Ribosomal; proteiny huseníčku; DNA, Plant; Mutation; inzerční mutageneze; DNA rostlinná; regulace genové exprese u rostlin; ribozomální DNA; restrukturace chromatinu; Telomere; telomery; faktor 1 pro uspořádání chromatinu; RNA ribozomální; Mutagenesis, Insertional; RNA, Ribosomal; Arabidopsis; Chromatin Assembly and Disassembly